The Nodo d'amore by Mario Ridolfi (diségno, 2021)
My memories of Mario Ridolfi are infinite in number, all of them as clear, even in the smallest details, as those we preserve of our loved ones, of our teachers.I can see him drawing Casa Lina and the Love knot in front of me; I always sat at the first table directly facing his desk.He drew with a fine-pointed Pelikan fountain pen on ‘carta burro,’ a translucent tracing paper of minimal thickness used for architectural drawings, that allows you to superimpose successive ideas and correct them.In his brown leather bag, Ridolfi kept his small bottle of black ink and a roll of this paper. I never saw him throw away any of the sheets of paper he had drawn on, not even the ones he rejected immediately because he was not satisfied with the solution.And I was there, in front of him, learning to draw perspective views and observing him... [read more]